One Health bootcamp - Becker, J.; Hassim, A.; Quan, M.; Fagir, D.M.; Conan, A.; Nkoana, T.; Mutua, Florence K.; Richards, Shauna; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2025)
One Health is an integrated, unifying approach that aims to sustainably balance and optimize the health of people, animals and ecosystems. The approach recognizes that the health of humans, domestic and wild animals, plants, and the wider environment (including ecosystems) are closely linked and interdependent.